2020
DOI: 10.1111/jdi.13431
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control before admission is an important determinant of prognosis in patients with coronavirus disease 2019

Abstract: Aims/Introduction This study aimed to explore the association between glycemic control before admission with severity and mortality of coronavirus disease 2019, and tried to reveal the mechanism. Materials and Methods A total of 77 inpatients were grouped into sufficient control group (glycated hemoglobin [HbA1c] <6.5%, n = 49) and insufficient control group (HbA1c ≥6.5%, n = 28). Regression models were used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“… 28 Another study compared patients with an HgbA1c ≥6.5% vs patients with an HgbA1c <6.5%. 29 The study demonstrated that patients with insufficient glycemic control (HgbA1c ≥6.5%) were more likely to be critically ill, develop ARDS, and suffer from secondary respiratory infections, when compared to patients with adequate glycemic control. 29 In addition, HgbA1c itself was independently associated with mortality.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“… 28 Another study compared patients with an HgbA1c ≥6.5% vs patients with an HgbA1c <6.5%. 29 The study demonstrated that patients with insufficient glycemic control (HgbA1c ≥6.5%) were more likely to be critically ill, develop ARDS, and suffer from secondary respiratory infections, when compared to patients with adequate glycemic control. 29 In addition, HgbA1c itself was independently associated with mortality.…”
Section: Discussionmentioning
confidence: 91%
“… 29 The study demonstrated that patients with insufficient glycemic control (HgbA1c ≥6.5%) were more likely to be critically ill, develop ARDS, and suffer from secondary respiratory infections, when compared to patients with adequate glycemic control. 29 In addition, HgbA1c itself was independently associated with mortality. 29 With regard to hospitalised patients, additional research demonstrated that patients with strict control of blood glucose levels (glycemic variability between 3.9 and 10.0 mmol/L) had reduced mortality compared to patients with poor blood glucose control (glycemic variability greater than 10.0 mmol/L).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, there are some studies that have shown that higher levels of HbA1c are associated with disease progression and mortality, while few studies have not. [6][7][8][9] These results highlight the relevant role of diabetes treatment regimen and glycemic control prior to COVID-19 infection and their association with poor outcomes. In Mexico, the COVID-19 pandemic has resulted in increased mortality rates due to the high burden of cardiometabolic diseases, which facilitate the development of severe COVID-19.…”
mentioning
confidence: 83%
“…Milionis et al, speculates that the increase in mortality rate of diabetic patients with COVID-19, could be related to the sustained activation of chronic inflammation [ 156 ]. Patients with COVID-19 and uncontrolled diabetes mellitus, defined by HbA1C levels > 6.5%, presented excessive uncontrolled inflammatory responses and hypercoagulable state, that lead to the development of acute respiratory distress syndrome which was associated with longer hospital stay and a greater probability of death compared to well-controlled diabetic patients (HbA1c < 6.5%) [ 157 , 158 ]. Currently, diabetes management goes beyond glycated hemoglobin (HbA1C) test because it does not take into account fluctuations in blood glucose levels known as glycemic variability (GV) which has been shown to have deleterious effects associated with endothelial dysfunction, characterized by increased expression of adhesion (ICAM-1, VCAM-1) and proinflammatory molecules (IL-8, NF-κB) [ 153 , 154 , 159 ].…”
Section: Impact Of Obesity and T2d In Covid-19 Patientsmentioning
confidence: 99%